Platypnea-orthodeoxia syndrome in patent foramen ovale and fenestrated atrial septal aneurysm with normal right atrial pressure: what is the culprit?. Issue 7 (1st July 2021) - Pelayo, Jerald; Shahzad, Anum; Peterson, Eric; Pressman, Gregg
Abstract : A 76-year-old Korean woman presented with intermittent episodes of exertional hypoxia at the rehabilitation facility after a recent admission for ischaemic stroke. Clinical and diagnostic investigation confirmed the presence of platypnea-orthodeoxia syndrome (POS). Transoesophageal echocardiogram revealed a patent foramen ovale and hyperdynamic interatrial septum with right-to-left intracardiac shunt. Further diagnostic workup did not reveal right atrial hypertension, cirrhosis, pulmonary hypertension or any other extracardiac causes of right-to-left shunt. Positional preferential blood flow from inferior vena cava to the left atrium due to counterclockwise displacement of interatrial septum with age and posture was postulated to explain the atrial right-to-left shunt and the resultant POS. Closure was performed using a cribriform amplatzer occluder which improved her symptoms.